Absence of parasympathetic denervation of the iris in alcoholics. - Myers, W (1979)
Forty patients with a history of alcohol abuse were treated with a 2% solution of methacholine to determine the prevalence of iridic parasympathetic denervation. Three (8%) of the alcoholics showed iris constriction of 1.0 mm or more, compared with three (8%) control subjects. In contrast, damage to the iridic parasympathetic nerve supply occurs in approximately 80% of patients with diabetes mellitus as determined by the same pharmacological technique.